Digital Transformation of Local MSMEs: Applying AI-Based Market Intelligence in Purwakarta (a Case Study at Ceramic Product) - M. Yani Syafei; Hetifah Sjaifudian; Siswanda H. Sumarto; Nuzul Husnah; Abdisamad Abdirahim Omar; Aceng Rohmana; Nelly (International Journal of Community Service (IJCS), 2026)
This international community service program aims to support the digital transformation of local Micro, Small, and Medium Enterprises (MSMEs) by applying AI-based market intelligence, focusing on ceramic product MSMEs in Purwakarta, Indonesia. The program was conducted using a participatory approach through training, practical mentoring, and evaluation involving lecturers, students, international academic partners, and MSME actors. The main objective was to enhance MSME capabilities in understanding market trends, identifying customer segments, analyzing competitors, and developing digital marketing strategies using artificial intelligence tools. The results indicate that participants experienced significant improvement in their understanding of digital transformation, shifting from basic social media usage toward a more comprehensive approach involving data-driven decision-making and market analysis. Through practical sessions, participants were able to generate customer personas, product positioning strategies, digital promotional content, and product descriptions using AI tools. The program also encouraged MSMEs to develop more adaptive and customer-oriented marketing approaches, particularly in promoting ceramic products as both functional and creative goods. In addition, the activity demonstrated that AI-based market intelligence can be applied effectively by MSMEs when delivered through simple, contextual, and practice-oriented methods. Despite initial challenges related to digital literacy and familiarity with AI tools, participants showed strong interest in adopting these technologies for their business development. The study concludes that integrating AI into MSME marketing practices can enhance competitiveness and market responsiveness. Continuous mentoring and collaboration between academic institutions and MSMEs are essential to ensure sustainable digital transformation and long-term business growth.